A construção da “marca” café do cerrado mineiro: inovações tecnológicas e estrutura de governança - Rabelo, Welber de Oliveira (2019)
Coffee production is one of the main branches of activity in Brazilian agriculture since the country is the world's largest coffee producer and this culture has been constantly present in Brazil's historical process. Because of such relevance, coffee growing has always had some kind of state support, which, however, changed in the 90's as the "Coffee Brazilian Institute" was extincted. The institute defended the national coffee production affairs. This event conducted to private socio-productive arrangements through organizations of coffee producers interests, such as the "Cerrado Coffee Growers Federation". Therefore, we can conclude that from the guide idea of coffee production it is constituted the “Cerrado Coffee Territory”. Another important result of this autonomous organization was the construction and acquisition of a certification through the ‘Cerrado Mineiro Denomination of Origin’, property of that Federation. This paper aims to analyze how the region is inserted in the context of coffee production and how the Federation acts in the territorial development of the "Cerrado". For this purpose, we disposed a theoretical framework looking for an explanation of this case, plus the utilization of primary data and econometrical exercises to verify if the use of certifications and of the denomination of origin contribute to increase the coffee-growing productivity. In conclusion, we emphasize that in the obtained sample the coffee producers with certification are more productive comparing to the others with the same observable features and that the participation of institutions through the process of certification and denomination of origin was beneficial to the development of coffee production in the ‘cerrado mineiro’, despite it was excluding in some aspects.